Oral atenolol compared to oral propranolol for infantile hemangioma - Victor Meza Viteri; Ligia Aranibar (Medwave, 2023)
Introduction Infantile hemangioma is the most frequent benign vascular tumor in childhood, with an incidence of 3 to 10%. When patients require treatment, oral propranolol, a non-selective lipophilic beta-blocker, is usually considered the therapy of choice. However, its use has been associated with several adverse events related to its β-2 action and its ability to cross the blood-brain barrier. Because of this, oral atenolol, a hydrophilic β-1 receptor-selective beta-blocker, may represent a valid treatment alternative. Nonetheless, there is still controversy regarding the efficacy and safety of atenolol when compared with propranolol as monotherapy for this condition.